A Fundamental Study of the Leaching Reactions Involved in the Caron Process - Michael J. Nicol (The Minerals, Metals and Materials Society, 2004)
This paper summarizes some of the results of a study of the reactions involved in the Caron leaching process and identifies the roles of the major dissolved species in the kinetics of dissolution of iron alloy particles formed during reductive roasting. Using rotating disk electrodes and synthetic leach solutions, the reduction of water with the evolution of hydrogen was found not to occur on a dissolving iron surface under typical leach conditions. It has been established that the oxidative dissolution is governed primarily by a reaction involving reduction of Co(III) to Co(II) ions. The reduction of oxygen was also found to make a significant but largely indirect contribution to the kinetics of the dissolution process. The dissolution rates of various iron-nickel-cobalt-copper alloys which simulate the dissolving alloy particles in a Caron plant were measured in synthetic leach solutions under aerobic and anaerobic conditions. The initial dissolution rates of iron, nickel and the iron alloys were found to increase in the presence of thiosulphate, whereas the thiosulphate had a negative effect on the dissolution rates of cobalt and copper. It is shown that the eventual passivation of the iron occurs sooner in solutions rich in Co(II) ions. Whilst these conditions are present in the quench slurry, on-site measurements have shown that due to the very high concentration of reduced dissolved species, passivation does not occur until the slurry is strongly aerated. In the light of these fundamental findings, options for optimizing the rate of dissolution and minimizing the extent of passivation of the iron and iron alloys are discussed. Keywords: Ammonia, leaching, alloy, kinetics, passivation.